The Relationship Between Waiting Time for Medication Services and Patient Satisfaction at The Pagelaran Community Health Center Pringsewu Regency Lampung Province - cemara, Septama Bagaskara; UAP, Mida Pratiwi; UAP, Vicko Suswidiantoro; UAP, Wisnu Probo Wijayanto (LPPM Universitas Dhyana Pura, 2025)
Patient satisfaction is a key indicator in assessing the quality of healthcare services, including pharmaceutical services. One factor that can affect the level of satisfaction is the length of waiting time, which is often a source of complaints at various public health centers. This research objective was to determine the level of patient satisfaction with the waiting time for medication services at Pagelaran Public Health Center. This research is a quantitative study using a survey method with a questionnaire that examines the correlation between medication service waiting time and patient satisfaction. The sample consisted of 96 respondents selected based on inclusion criteria, which included: patients aged 17–65 years, willing to participate as respondents, able to read and write, and having received pharmaceutical services. Exclusion criteria included incomplete questionnaires and incomplete respondent data. Based on the research results, the majority of respondents stated they agreed (57%), strongly agreed (42%), and only 1% disagreed with the medication service waiting time at Pagelaran Public Health Center. Regarding service satisfaction, the average score across five indicators of medication service satisfaction reached 82%, which falls into the “very satisfied” category. The five indicators included: reliability (83%), responsiveness (76%), assurance (97%), empathy (75%), and tangible evidence (77%). The overall average satisfaction level across the five indicators was 82%, categorized as very satisfied. The conclusion of this research indicates that the medication services provided by Pagelaran Public Health Center have met the expectations of the majority of patients. The chi-square test result was 0.000, indicating a significant correlation between the waiting time for medication services and patient satisfaction at Pagelaran Public Health Center .